The Effect of Aerobic Exercise on Neuroplasticity within the Motor Cortex following Stroke. - Kate Murdoch; Jonathan D Buckley; Michelle N McDonnell (PLoS ONE)
Background Aerobic exercise is associated with enhanced plasticity in the motor cortex of healthy individuals, but the effect of aerobic exercise on neuroplasticity following a stroke is unknown. Objective The aim of this study was to compare corticomotoneuronal excitability and neuroplasticity in the upper limb cortical representation following a single session of low intensity lower limb cycling, or a rest control condition. Methods We recruited chronic stroke survivors to take part in three experimental conditions in a randomised, cross-over design. Corticomotoneuronal excitability was examined using transcranial magnetic stimulation to elicit motor evoked potentials in the affected first dorsal interosseus muscle. Following baseline measures, participants either cycled on a stationary bike at a low exercise intensity for 30 minutes, or remained resting in a seated position for 30 minutes. Neuroplasticity within the motor cortex was then examined using an intermittent theta burst stimulation (iTBS) paradigm. During the third experimental condition, participants cycled for the 30 minutes but did not receive any iTBS. Results Twelve participants completed the study. We found no significant effect of aerobic exercise on corticomotoneuronal excitability when compared to the no exercise condition (P > 0.05 for all group and time comparisons). The use of iTBS did not induce a neuroplastic-like response in the motor cortex with or without the addition of aerobic exercise. Conclusions Our results suggest that following a stroke, the brain may be less responsive to non-invasive brain stimulation paradigms that aim to induce short-term reorganisation, and aerobic exercise was unable to induce or improve this response.